Periodic DFT study of molecular crystals - Rivera Escobar, R. (2013)
Two molecular crystals have been studied using the first-principles density functional theory calculations within the generalized gradient approximation (GGA). It was found that the Perdew-Burke-Ernzerhof (PBE) GGA exchange-correlation functionals are adequate for the mentioned systems. Obtained results show that it is possible to reproduce very well the geometry of at least some molecular crystals if computational parameters are chosen adequately. In addition to reproducing crystalline structures of the compounds in close agreement with the available experimental data, the present work reports analysis on the chemical bonding in the materials and gives total and partial density of states of these molecular crystals for the first time.